From depressive symptoms to suicide risk: Roles of sense of belongingness and acquired capability for suicide in patients with mental disorders. Issue 2 (16th January 2020) - Wang, Shengnan; Li, Congcong; Jia, Xuji; Lyu, Juncheng; Wang, Yanyu; Sun, Hongwei
Abstract: In order to prevent suicides in patients with mental disorders, it was critical to recognize the risk factors and explore the mechanism. Based on depressive symptoms, which were common in patients with mental disorders in consolidation period in China, we constructed a moderated mediating model under the framework of Integrated Motivational‐Volitional Model of suicidal behaviour, and examined the mechanism of how depressive symptoms, thwarted belongingness, and acquired capability for suicide influenced suicide risk. In this study, data were collected from 164 patients through four questionnaires, and analyzed with PROCESS macro for SPSS (Hayes, 2008). The result showed that in the predictive effects of depressive symptoms on suicide risk, thwarted belongingness was a partial mediating variable, while acquired capability for suicide played a moderating role in the partial mediating model. Specifically, the predictive effects of depressive symptoms and thwarted belongingness, both as motivation variables, on suicide risk both occurred in the case of the high acquired capability of suicide, which was a volition variable. The research pointed out the interdependence of depressive symptoms and a sense of belongingness, and clarified the critical role of acquired capability for suicide. The integrated perspective could enhance the interpretation of reality, and enlightened those carrying out the practice of suicide intervention to patients with mental disorders.